Intrapartum Synthetic Oxytocin and Its Effects on Maternal Well‐Being at 2 Months Postpartum. Issue 1 (10th November 2015) - Gu, Vivian; Feeley, Nancy; Gold, Ian; Hayton, Barbara; Robins, Stephanie; Mackinnon, Anna; Samuel, Simcha; Carter, C. Sue; Zelkowitz, Phyllis
Abstract: Background: Synthetic oxytocin (synOT) is commonly used in labor management to induce and augment labor, and to prevent postpartum hemorrhage. However, its long‐term consequences for maternal health and behavior are largely understudied. We examined the relationship between synOT and maternal oxytocin levels, breastfeeding, and maternal mental health at 2 months postpartum. Methods: Women were recruited during pregnancy or within 48 hours of giving birth through obstetric practices and hospitals. A total of 386 women were visited in their homes at 2 months postpartum, where they completed questionnaires assessing breastfeeding, depression, anxiety, posttraumatic stress, and somatization. Oxytocin levels were obtained from blood samples and synOT dosage information was gathered from hospital charts. Results: Intrapartum synOT dose was positively correlated with endogenous oxytocin levels at 2 months postpartum. Women who were exclusively breastfeeding at 2 months postpartum had received significantly less synOT compared with their nonexclusively breastfeeding counterparts. Higher synOT dose was associated with greater depressive, anxious, and somatization symptoms. SynOT dose was not associated with perinatal posttraumatic stress. Conclusions: The widespread use of synOT in managed labor warrants caution, as the influence of synOT on a new mother's well‐being is evident at 2 months postpartum.